Identifying Perturbations That Tipped the Stratosphere Into a Sudden Warming During January 2013 - Chris Kent; Adam A. Scaife; William J. M. Seviour; Nick Dunstone; Doug Smith; Kerry Smout‐Day (Geophysical Research Letters, 2023)
Abstract We present a new methodology demonstrating that specific small‐magnitude regional perturbations can cause large systematic responses in subseasonal predictions. We show this with ensemble forecasts of the January 2013 Sudden Stratospheric Warming (SSW) from an operational long‐range global prediction system. In forecast members which predict the SSW, tropospheric ridging over the North Atlantic is strengthened 10 days prior to the event. This subsequently enhances planetary wave forcing and weakens the stratospheric polar vortex. Transplanting tropospheric conditions in this region from “correct” to “incorrect” forecasts (and vice versa) significantly alters the SSW forecast probability. The occurrence of this SSW is therefore strongly controlled by the troposphere several days prior. Tipping more members into a sudden warming also significantly affects surface predictions the following month. Despite chaotic behavior of the climate system, small‐magnitude synoptic‐scale perturbations can drive different dynamical states and systematically impact medium and long‐range predictions.